2020
DOI: 10.1167/tvst.9.11.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravitreal Aflibercept on Retinal Function and Improvement of Macular Edema Associated With Diabetic Retinopathy

Abstract: Effects of intravitreal aflibercept on retinal function and improvement of macular edema associated with diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The 30-Hz flicker ERG is the response of the cones (8), where the density of cone cells in the macular fovea is higher (27); therefore, only if the entire retina or the macula is involved, there is a significant change. In other words, if the macula is involved, the test becomes more sensitive and helpful to evaluate the effectiveness of treatment (28). In addition, traditional ERG examinations required dark adaptation (8) and were time consuming, while a 30-Hz flicker ERG check can be done in a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The 30-Hz flicker ERG is the response of the cones (8), where the density of cone cells in the macular fovea is higher (27); therefore, only if the entire retina or the macula is involved, there is a significant change. In other words, if the macula is involved, the test becomes more sensitive and helpful to evaluate the effectiveness of treatment (28). In addition, traditional ERG examinations required dark adaptation (8) and were time consuming, while a 30-Hz flicker ERG check can be done in a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…[82][83][84] The retinal sensitivity improvement was significantly correlated with the BCVA and inversely correlated with the OCT central subfield thickness. [85][86][87][88] In addition, Santos and colleagues reported that better retinal sensitivities before treatment were associated with better BCVA outcomes after therapy. This suggested that the baseline MP findings may have prognostic value for DME treatments.…”
Section: Microperimetry In Diabetic Retinopathymentioning
confidence: 99%
“…For example, in diabetic macular edema (DME), the retinal sensitivities determined by MP coupled with optical coherence tomography (OCT) biomarkers and multifocal electroretinograms are used as functional markers for the entire macula region. Thus, earlier studies have shown that MP, together with these other methods, were able to show improvements in sensitivity following anti-VEGF therapy by ranibizumab or aflibercept in eyes with DME 6,7. Furthermore, the macular function assessed by MP combined with structural OCT angiography (OCTA) metrics and capillary dropout areas showed low sensitivities in eyes with ischemic DME 8.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations